Research Practice of Participatory Skills to Interpret The Principles of Buddhism and The Art of Young Contemporary Thailand with The Format of The Art Competitions - Thanatip Thipwaree (TAMA: Journal of Visual Arts, 2024)
Abstract This article is part of The Research Practice of Participatory Skills to Interpret The Principles of Buddhism and The Art of Young Contemporary Thailand with The Format of The Art Competitions. The objective is to enable students and young people to apply the philosophy, concepts, teachings, beliefs and attitudes of Buddhism to create works of art. Through organizing a contest and exhibiting works of art in the name "Interpret Buddhism through the new generation" Which has been conceptualized from the research. Interpretation of Buddhist Teachings and the Creation of Contemporary art. With the assumption from this concept that Will be able to promote the skills of interpreting Buddhist principles in Thai society. And from the survey of youth's understanding of the creation of artistic works under religious topics It appears as a total of 84 works submitted to the event in both 2D and 3D categories, which were analyzed and summarized in descriptive research. This research project aims to stimulate target groups of youth and young people in Thai society. Interested in studying and interpreting the valuable principles of Buddhism and being able to truly apply that value in life. Inevitably brings benefits to a peaceful coexistence in Thai society. Conclusion from the operation of the research project as a platform that allows students or young artists to express themselves through the creation and dissemination of their works of art. Able to identify creative potential and skill in interpreting Buddhist principles from various perspectives, interesting and different among youth groups today (2019).